İBNİ HALDUN VE THOMAS HOBBES'UN SİYASET FELSEFELERİNDE DEVLET - ÜNALIR, MÜRŞİT (Fırat Üniveristesi, 2015)
İbni Haldun kendi felsefesini toplum üzerine kurar. İlm-i Umran ve Asabiyyet kavramları ile de toplumsal yaşam ve örgütlenmesinin ortaya çıkardığı her türlü olay ve kurumu inceleme konusu yapar. Bu sonuçlardan biri de devlettir. İbni Haldun devleti toplumdan ayrıştırarak incelemez. Organizmacı bir yaklaşımla, devletlerin de tıpkı insanlar gibi sınırlı bir ömre sahip olduğunu ifade ederek en temelde Asabiyyet kuramı üzerine şekillendirir. Thomas Hobbes ise insanların meydana getirdiği yapay bir kurum olarak ortaya çıkan devleti, faydacı bir yaklaşımla bireylere dayandırır. Hobbes insan doğasından hareketle, toplumsal sözleşmeye ve oradan da mutlak iktidara doğru giden devlet anlayışını, bireylerin güvenlik ve barışa olan ihtiyaçları ve talepleri doğrultusunda açıklamaya çalışır. Anahtar kelimeler: Asabiyyet, Umran, Doğa Durumu, Toplumsal Sözleşme, Devlet

Ibn Khaldun builds his philosophies upon society. By ilm-i Umran and nervousness concepts, he makes all kinds of events and institutions that revealed by social life and its organization a subject of study. One of these results is the state. Ibn Khaldun does not examine the state by separating it from the society. By an organismic approach, Ibn Khaldun who states that the states have a limited life just as human being was founded his understanding of the state basically on the nervousness doctrine. On the other hand, by a utilitarian approach Thomas Hobbes has attributed the emerging of the state as an artificial institution that created by human to individuals. Starting from human nature to social contract and from there to the absolute power Hobes tries to explain the understanding of the state in the direction of individuals' needs and demands for safety and peace. Key words: Nervousness, Umran, Nature Condition, Social Contract, State
State in the political philosophies of İbn Khaldun and Thomas Hobbes
Keywords: Felsefe